Pre and postnatal exposure to mercury and sexual development in 9-year-old children in Spain: The role of brain-derived neurotrophic factor - Sarzo, Blanca; Ballester, Ferran; Soler-Blasco, Raquel; Lopez-Espinosa, Maria-Jose; Lozano, Manuel; Iriarte, Gorka; Beneito, Andrea; Riutort-Mayol, Gabriel; Murcia, Mario; Llop, Sabrina (Environmental research, 2022)
Early exposure to mercury has been related to endocrine disruption. Steroid hormones play a crucial role in neural cell migration, differentiation, etc., as well as protecting against several neurotoxic compounds. We investigate the relation between mercury exposure and children's sexual development, and we evaluate the possible influence of different brain-derived neurotrophic factor (BDNF) polymorphisms on this association. Our study sample comprised 412 9-year-old children participating in the INMA cohort (2004–2015). Mercury concentrations were measured at birth (cord blood) and at 4 and 9 years of age (hair). Sexual development was assessed by levels of sex steroid hormones (estradiol and testosterone) in saliva and the Tanner stages of sex development at 9 years (categorized as 1: prepuberty and >1: pubertal onset). Covariates and confounders were collected through questionnaires during pregnancy and childhood. Polymorphisms in the BDNF gene were genotyped in cord blood DNA. Multivariate linear regression analyses were performed between mercury levels and children's sexual development by sex. Effect modification by genetic polymorphisms and fish intake was assessed. We found marginally significant inverse associations between postnatal exposure to mercury (at 9 years) and testosterone levels (β[95%CI] = -0.16[-0.33,0.001], and −0.20[-0.42,0.03], for boys and girls, respectively). Additionally, we found that prenatal mercury was negatively associated with Tanner stage >1 in boys. Finally, we found significant genetic interactions for some single nucleotide polymorphisms in the BDNF gene. In conclusion, pre and postnatal exposure to mercury seems to affect children's sexual development and BDNF may play a role in this association, but further research would be needed. •We study the relation between mercury exposure and child sexual development and the influence of different BDNF polymorphisms.•Inverse associations between postnatal exposure to mercury (at 9 years) and testosterone levels for both sexes.•Prenatal mercury exposure was negatively associated with being in a pubertal onset in boys.•Significant interactions for some BDNF polymorphisms on the association between mercury and both sex steroid hormones and Tanner staging.